2021
DOI: 10.1038/s41398-021-01680-5
|View full text |Cite
|
Sign up to set email alerts
|

A missense variant in SHARPIN mediates Alzheimer’s disease-specific brain damages

Abstract: Established genetic risk factors for Alzheimer’s disease (AD) account for only a portion of AD heritability. The aim of this study was to identify novel associations between genetic variants and AD-specific brain atrophy. We conducted genome-wide association studies for brain magnetic resonance imaging measures of hippocampal volume and entorhinal cortical thickness in 2643 Koreans meeting the clinical criteria for AD (n = 209), mild cognitive impairment (n = 1449) or normal cognition (n = 985). A missense var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 73 publications
(81 reference statements)
0
11
0
Order By: Relevance
“…Among them, the G186R and R274W variants of SHARPIN reportedly suppressed TNF-α-mediated NF-κB activation and generated aberrant granular clumps in HEK293T cells ( Asanomi et al, 2019 ; Asanomi et al, 2022 ). Moreover, the R274W variant of SHARPIN shows a weaker interaction with HOIP ( Park et al, 2021 ). As an etiology of AD, SHARPIN reportedly regulates Aβ phagocytosis, inflammation, and cell death in macrophages by linking to the NLRP3 inflammasome in response to Aβ ( Krishnan et al, 2020 ).…”
Section: Heterologous Ubiquitin Chains In Neurodegenerative Disease I...mentioning
confidence: 99%
See 2 more Smart Citations
“…Among them, the G186R and R274W variants of SHARPIN reportedly suppressed TNF-α-mediated NF-κB activation and generated aberrant granular clumps in HEK293T cells ( Asanomi et al, 2019 ; Asanomi et al, 2022 ). Moreover, the R274W variant of SHARPIN shows a weaker interaction with HOIP ( Park et al, 2021 ). As an etiology of AD, SHARPIN reportedly regulates Aβ phagocytosis, inflammation, and cell death in macrophages by linking to the NLRP3 inflammasome in response to Aβ ( Krishnan et al, 2020 ).…”
Section: Heterologous Ubiquitin Chains In Neurodegenerative Disease I...mentioning
confidence: 99%
“…In the crystal structure, the electron density of R274 of SHARPIN was unclear, and its side chain did not form hydrogen bonds or salt bridges with HOIP UBA1. However, a molecular dynamics (MD) simulation suggested that SHARPIN R274 forms hydrogen bonds and salt bridges with E487 and Q490 of HOIP, and the R274W mutation destabilizes the complex at the interface ( Park et al, 2021 ). This simulation was validated by co-immunoprecipitation assays, which showed that the binding between SHARPIN UBL (R274W) and HOIP UBA1-UBA2 was significantly reduced, as compared with that of SHARPIN UBL WT ( Park et al, 2021 ).…”
Section: Heterologous Ubiquitin Chains In Neurodegenerative Disease I...mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent genetic evidence of potential loss-of-function mutants involved in NF-κB signaling of AD patients might provide a genetic reason for this early correlation ( Bellenguez et al, 2022 ). In this line, human SHARPIN mutants were shown to have less capability of NF-κB activation ( Park et al, 2021 ). Furthermore, SHARPIN mutants ( Park et al, 2021 ) of the LUBAC complex are highly significantly correlated with a reduction in the thickness of the entorhinal cortex, one of the earliest signs of AD ( Kobro-Flatmoen et al, 2021 ; Figures 3A,B ).…”
Section: Germline Mutations Affecting Nf-κb Activation In the Context...mentioning
confidence: 99%
“…In this line, human SHARPIN mutants were shown to have less capability of NF-κB activation ( Park et al, 2021 ). Furthermore, SHARPIN mutants ( Park et al, 2021 ) of the LUBAC complex are highly significantly correlated with a reduction in the thickness of the entorhinal cortex, one of the earliest signs of AD ( Kobro-Flatmoen et al, 2021 ; Figures 3A,B ). Soheili-Nezhad et al (2020) identified a SHARPIN mutant in AD associated with degeneration of the limbic system and its interconnecting white-matter.…”
Section: Germline Mutations Affecting Nf-κb Activation In the Context...mentioning
confidence: 99%